Method for preparing near-infrared shielding coating with high visible light transmittance
By mixing HxWO3·2H2O blue powder solution with polyvinyl butyral ester powder to form a hydrogen tungsten bronze hydrate glass coating, the near-infrared shielding performance of existing cesium tungsten bronze materials in high visible light transmittance scenarios is solved. The problem of insufficient results enables higher visible light transmittance and ultraviolet shielding.
Patent Information
- Application Number
- CN202411678333.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-22
AI Technical Summary
The existing cesium tungsten bronze materials perform poorly in high visible light transmittance scenarios, especially in applications such as automotive front glass, which is difficult to meet the simultaneous improvement of near-infrared shielding and visible light transmittance.
The HxWO3·2H2O blue powder solution was mixed with polyvinyl butyral ester powder, and applied to the glass surface by spin coating to form a hydrogen tungsten bronze hydrate glass coating. The method includes pretreatment, preparation of precursor solutions, high temperature reaction and separation and washing steps, and prepares a HxWO3·2H2O blue powder solution with a particle size of 5-100 nm.
The prepared hydrogen tungsten bronze hydrate coating not only has excellent near-infrared shielding characteristics, but also has a significantly better transmittance in the visible light region than the cesium tungsten bronze coating, and the ultraviolet shielding rate is also higher, making it suitable for large-scale production.
Smart Images

Figure CN119192918B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass transparent heat-insulating coatings, and more specifically, to a method for preparing a near-infrared shielding coating with high visible light transmittance. Background Art
[0002] Near-infrared light contributes nearly 50% to the thermal radiation energy of the solar spectrum. In the hot summer, this part of the thermal radiation brings a lot of cooling energy consumption to buildings or cars. Therefore, the development of low-cost, high-performance transparent thermal insulation materials and coatings for windows has significant economic and social benefits and excellent development prospects. At present, tungsten bronze material is an excellent near-infrared shielding material, among which alkali metal tungsten bronze such as cesium or sodium performs well in visible light transmittance and near-infrared shielding performance, so it is widely used in the field of transparent thermal insulation film. Among them, the patent application number CN201910699087.9 discloses a method for preparing cesium tungsten bronze material at normal pressure, which discloses that cesium tungsten bronze material is prepared within 1 hour under normal pressure and 40-78°C conditions using tungsten hexachloride as a tungsten source and cesium hydroxide as a cesium source; the patent application number CN202311523822.3 discloses a method for preparing ultrafine cesium tungsten bronze powder, which discloses that the tungsten source, the cesium source and the organic solvent are mixed and kept warm at 80-150°C, and then reacted at 100-300°C to obtain cesium tungsten bronze powder; although the above patents disclose the synthesis of cesium tungsten bronze, and although cesium tungsten bronze has excellent near-infrared shielding performance and good visible light transmittance, it still does not meet the needs of some high visible light transmittance scenes, such as car windshields. In order to solve this technical shortcoming, the present application provides a method for preparing a near-infrared shielding coating with high visible light transmittance. The prepared hydrogen tungsten bronze hydrate coating not only has excellent near-infrared shielding properties, but also has a transmittance in the visible light region that is significantly better than that of the cesium tungsten bronze coating, and a higher ultraviolet shielding rate than that of the cesium tungsten bronze. Summary of the invention
[0003] In view of the shortcomings of the prior art, the object of the present invention is to provide a method for preparing a near-infrared shielding coating with excellent near-infrared shielding properties and high visible light transmittance suitable for large-scale production.
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing a near-infrared shielding coating with high visible light transmittance, comprising the following steps: x The WO3·2H2O blue powder solution and the polyvinyl butyral ester powder are fully mixed in a mass ratio of 1:5-10 to obtain a slurry, and then the slurry is spin-coated on the surface of a glass sample and finally dried to obtain a glass coating, wherein 0≤x≤1.
[0005] Furthermore, the Hx The particle size of WO3·2H2O blue powder is 5-100nm.
[0006] Furthermore, the H x The preparation method of WO3·2H2O blue powder solution is as follows:
[0007] (1) Pretreatment: LaO3H3 powder and benzyl alcohol are mixed in a mass ratio of 1:500-1000, and stirred until the LaO3H3 powder is completely dissolved to obtain a LaO3H3 solution;
[0008] (2) Preparing a precursor solution: mixing the LaO3H3 solution in step (1) with the WCl6 raw material in a mass ratio of 20-40:1, and mixing by magnetic stirring to obtain a precursor solution;
[0009] (3) High temperature reaction: placing the precursor solution in step (2) in a reaction kettle, and then placing the reaction kettle in a microwave synthesizer, reacting under the combined action of hydrothermal and microwave, the reaction temperature is 50-200°C, the reaction time is 5-240min, and then naturally cooling to room temperature to obtain a reaction solution;
[0010] (4) Separation and washing: The reaction solution in step (3) is centrifuged, and the separated solid is then washed with deionized water, anhydrous ethanol, dilute sulfuric acid, ionized water and anhydrous ethanol in sequence to obtain the H x WO3·2H2O blue powder solution.
[0011] Furthermore, the stirring conditions in step (1) are as follows: the stirring speed is 100-800 r / min. Too low a stirring speed leads to uneven mixing of the solution, insufficient contact between LaO3H3 and WCl6, affecting the reaction rate and uneven morphology of the product; too high a stirring speed may cause excessive evaporation of the solvent or local overheating, thereby affecting the quality of the product; too short a stirring time may lead to incomplete mixing of the precursor solution and insufficient reaction, resulting in poor crystallinity, uneven particle size or low yield of the reaction product; too long a stirring time may cause evaporation of the solvent or increase the risk of mechanical damage, resulting in reduced stability of the reaction system.
[0012] Furthermore, the stirring conditions in step (2) are: stirring speed is 100-800 r / min, and stirring time is 10-60 min.
[0013] Furthermore, the centrifugal separation conditions in step (4) are: speed of 3000-5000 r / min, time of 2-10 min. Too low a centrifugal speed cannot effectively separate the precipitate, resulting in an incomplete washing process, which may cause the residual solvent or reaction by-products to affect the subsequent reaction and the purity of the particles; too high a centrifugal speed may cause the particles to agglomerate, affecting the final particle size and distribution; too short a centrifugal time may cause the solids to not settle sufficiently, affecting the subsequent washing efficiency, and thus failing to effectively remove impurities in the solvent; too long a centrifugal time may cause the solid particles to compact or agglomerate, making it difficult to redisperse or affecting the morphology of the particles.
[0014] Furthermore, the method of washing with deionized water in step (4) is as follows: the separated solids are washed with deionized water in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0015] Furthermore, the method of washing with anhydrous ethanol in step (4) is as follows: the separated solid and anhydrous ethanol are washed in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0016] Furthermore, the method of washing with dilute sulfuric acid in step (4) is as follows: the separated solid is washed with dilute sulfuric acid having a concentration of 20-30% in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0017] The advantages of the present invention are:
[0018] 1. The present invention discloses a method for preparing a near-infrared shielding coating with high visible light transmittance, wherein H x WO3·2H2O blue powder solution is mixed with polyvinyl butyral ester powder and coated on the surface of the glass sample to form hydrogen tungsten bronze hydrate glass coating, which not only has excellent near-infrared shielding properties, but also has significantly better transmittance in the visible light region than cesium tungsten bronze coating, and the shielding rate of ultraviolet rays is also better than that of cesium tungsten bronze coating.
[0019] 2. The present invention discloses a method for preparing a near-infrared shielding coating with high visible light transmittance, wherein the preparation of H x The method of preparing WO3·2H2O blue powder solution is simple, easy to operate, less time-consuming, low-cost, and suitable for large-scale production. x WO3·2H2O blue powder solution can be directly mixed with polyvinyl butyral ester powder for coating glass without drying, which is convenient to use. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is H of Example 1 of the present invention x XRD pattern of WO3·2H2O blue powder;
[0021] Figure 2 is H of Example 1 of the present invention x SEM image of WO3·2H2O blue powder;
[0022] Figure 3 1 is a transmittance curve diagram of the glass coating of Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION
[0023] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0024] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs.
[0025] In the present invention, unless otherwise specified, the directions used, such as "up" and "down", usually refer to the directions shown in the drawings, or to the vertical, perpendicular or gravity directions; similarly, for ease of understanding and description, "left" and "right" usually refer to the left and right shown in the drawings; "inside" and "outside" refer to the inside and outside relative to the outline of each component itself, but the above-mentioned directions are not used to limit the present invention.
[0026] Example 1: A method for preparing a near-infrared shielding coating with high visible light transmittance, comprising the following steps: 100 mL of 5% H x The WO3·2H2O blue powder solution was fully mixed with 37.5 g of polyvinyl butyral ester powder to obtain a slurry, which was then applied to the surface of a glass sample by spin coating and finally dried to obtain a glass coating, where 0≤x≤1. x The particle size of WO3·2H2O blue powder is 5-100nm.
[0027] Among them, H x The preparation method of WO3·2H2O blue powder solution is as follows:
[0028] (1) Pretreatment: 0.0779 g of LaO3H3 powder was mixed with 50 ml of benzyl alcohol and stirred until the LaO3H3 powder was completely dissolved to obtain a LaO3H3 solution; the stirring speed was 100-800 r / min.
[0029] (2) Preparing a precursor solution: The LaO3H3 solution in step (1) is mixed with 1.6260 g of WCl6 raw material, and the mixture is mixed by magnetic stirring to obtain a precursor solution; wherein the stirring speed is 100-800 r / min, and the stirring time is 10-60 min.
[0030] (3) High temperature reaction: placing the precursor solution in step (2) in a reaction kettle, and then placing the reaction kettle in a microwave synthesizer to react under the combined action of hydrothermal and microwave, the reaction temperature is 50-200°C, the reaction time is 5-240min, and then naturally cooled to room temperature to obtain a reaction solution;
[0031] (4) Separation and washing: The reaction solution in step (3) is centrifuged at a speed of 3000-5000 r / min for 2-10 min; the separated solid is then washed with deionized water, anhydrous ethanol, dilute sulfuric acid, ionized water and anhydrous ethanol in sequence to obtain H x WO3·2H2O blue powder solution. The powder was analyzed by X-ray diffractometer. The results are as follows Figure 1 As shown. Figure 1 It can be seen that the diffraction peak position of the prepared powder is consistent with H 0.12 The standard card of WO3·2H2O PDF Card: 40-0693 is in good agreement. At the same time, the microstructure of the powder was observed by scanning electron microscopy (SEM). The results are as follows Figure 2 As shown. Figure 2 It can be seen that the H obtained in Example 1 x WO3·2H2O blue powder has uniform particle size distribution and excellent dispersibility, and the particle size distribution is 10-40nm.
[0032] The specific method of washing with ionized water is as follows: the separated solids are washed with deionized water in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a rotation speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0033] The specific method of washing with anhydrous ethanol is as follows: the solid separated by washing with ionized water and anhydrous ethanol are washed in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge with a rotation speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0034] The specific method of washing with dilute sulfuric acid is as follows: the solid separated by washing with anhydrous ethanol is cleaned in an ultrasonic cleaner with dilute sulfuric acid with a concentration of 20-30% for 5-30 minutes, and then placed in a centrifuge with a rotation speed of 3000-5000r / min for centrifugation for 2-10 minutes.
[0035] The present invention prepares Hx The method of preparing WO3·2H2O blue powder solution is simple, easy to operate, less time-consuming, low-cost, and suitable for large-scale production. x WO3·2H2O blue powder solution can be directly mixed with polyvinyl butyral ester powder for coating glass without drying, which is convenient to use.
[0036] Example 2: A method for preparing a near-infrared shielding coating with high visible light transmittance, comprising the following steps: mixing 100 mL of 1% H x The WO3·2H2O blue powder solution was fully mixed with 5 g of polyvinyl butyral ester powder to obtain a slurry, which was then applied to the surface of a glass sample by spin coating and finally dried to obtain a glass coating, where 0≤x≤1. x The particle size of WO3·2H2O blue powder is 5-100nm.
[0037] Among them, H x The preparation method of WO3·2H2O blue powder solution is as follows:
[0038] (1) Pretreatment: 0.2000 g of LaO3H3 powder was mixed with 100 mL of benzyl alcohol and stirred until the LaO3H3 powder was completely dissolved to obtain a LaO3H3 solution; wherein the stirring speed was 100-800 r / min.
[0039] (2) Preparing a precursor solution: Mix the LaO3H3 solution in step (1) with 5.0100 g of WCl6 raw material, and obtain a precursor solution by magnetic stirring; wherein the stirring speed is 100-800 r / min, and the stirring time is 10-60 min.
[0040] (3) High temperature reaction: placing the precursor solution in step (2) in a reaction kettle, and then placing the reaction kettle in a microwave synthesizer to react under the combined action of hydrothermal and microwave, the reaction temperature is 50-200°C, the reaction time is 5-240min, and then naturally cooled to room temperature to obtain a reaction solution;
[0041] (4) Separation and washing: The reaction solution in step (3) is centrifuged at a speed of 3000-5000 r / min for 2-10 min; the separated solid is then washed with deionized water, anhydrous ethanol, dilute sulfuric acid, ionized water and anhydrous ethanol in sequence to obtain H x WO3·2H2O blue powder solution.
[0042] The specific method of washing with ionized water is as follows: the separated solids are washed with deionized water in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a rotation speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0043] The specific method of washing with anhydrous ethanol is as follows: the solid separated by washing with ionized water and anhydrous ethanol are washed in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge with a rotation speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0044] The specific method of washing with dilute sulfuric acid is as follows: the solid separated by washing with anhydrous ethanol is cleaned in an ultrasonic cleaner with dilute sulfuric acid with a concentration of 20-30% for 5-30 minutes, and then placed in a centrifuge with a rotation speed of 3000-5000r / min for centrifugation for 2-10 minutes.
[0045] The present invention prepares H x The method of preparing WO3·2H2O blue powder solution is simple, easy to operate, less time-consuming, low-cost, and suitable for large-scale production. x WO3·2H2O blue powder solution can be directly mixed with polyvinyl butyral ester powder for coating glass without drying, which is convenient to use.
[0046] Example 3: A method for preparing a near-infrared shielding coating with high visible light transmittance, comprising the following steps: 100 mL of 10% H x The WO3·2H2O blue powder solution was fully mixed with 10 g of polyvinyl butyral ester powder to obtain a slurry, which was then applied to the surface of a glass sample by spin coating and finally dried to obtain a glass coating, where 0≤x≤1. x The particle size of WO3·2H2O blue powder is 5-100nm.
[0047] Among them, H x The preparation method of WO3·2H2O blue powder solution is as follows:
[0048] (1) Pretreatment: 0.1500 g of LaO3H3 powder was mixed with 150 mL of benzyl alcohol and stirred until the LaO3H3 powder was completely dissolved to obtain a LaO3H3 solution; wherein the stirring speed was 100-800 r / min.
[0049] (2) Preparing a precursor solution: The LaO3H3 solution in step (1) is mixed with 3.7537 g of WCl6 raw material, and the mixture is mixed by magnetic stirring to obtain a precursor solution; wherein the stirring speed is 100-800 r / min, and the stirring time is 10-60 min.
[0050] (3) High temperature reaction: placing the precursor solution in step (2) in a reaction kettle, and then placing the reaction kettle in a microwave synthesizer to react under the combined action of hydrothermal and microwave, the reaction temperature is 50-200°C, the reaction time is 5-240min, and then naturally cooled to room temperature to obtain a reaction solution;
[0051] (4) Separation and washing: The reaction solution in step (3) is centrifuged at a speed of 3000-5000 r / min for 2-10 min; the separated solid is then washed with deionized water, anhydrous ethanol, dilute sulfuric acid, ionized water and anhydrous ethanol in sequence to obtain H x WO3·2H2O blue powder solution.
[0052] The specific method of washing with ionized water is as follows: the separated solids are washed with deionized water in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a rotation speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0053] The specific method of washing with anhydrous ethanol is as follows: the solid separated by washing with ionized water and anhydrous ethanol are washed in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge with a rotation speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
[0054] The specific method of washing with dilute sulfuric acid is as follows: the solid separated by washing with anhydrous ethanol is cleaned in an ultrasonic cleaner with dilute sulfuric acid with a concentration of 20-30% for 5-30 minutes, and then placed in a centrifuge with a rotation speed of 3000-5000r / min for centrifugation for 2-10 minutes.
[0055] The present invention prepares H x The method of preparing WO3·2H2O blue powder solution is simple, easy to operate, less time-consuming, low-cost, and suitable for large-scale production. x WO3·2H2O blue powder solution can be directly mixed with polyvinyl butyral ester powder for coating glass without drying, which is convenient to use.
[0056] Comparative Example 1: 0.377 g of CsOH∙H2O and 150 mL of benzyl alcohol solution were stirred and mixed for 20 minutes, and then 0.9 g of WCl6 was added to keep the concentration of WCl6 in the precursor solution at 0.015 M. The solution was then transferred to a high-pressure reactor and reacted at 200 °C for 4 hours. Finally, the product was washed with deionized water and alcohol several times to obtain cesium tungsten bronze Cs 0.33 WO3 solution, 37.5 g of polyvinyl butyral ester powder was added into the solution and mixed thoroughly to obtain a slurry, and then the slurry was applied on the surface of the glass sample by spin coating, and finally dried to obtain a glass coating.
[0057] Experiment: The glass coatings prepared in Example 1 and Comparative Example 1 were tested for transmittance using a UV-Vis-NIR photometer (instrument model: UH4150). The results are as follows: Figure 3 As shown, from Figure 3 It can be seen that, compared with the glass coating prepared in Comparative Example 1, the glass coating prepared in Example 1 has a wider range of transmittance in the visible light region and a lower transmittance in the ultraviolet region below 400nm. x Compared with cesium tungsten bronze coating, WO3·2H2O glass coating has better visible light transmittance and ultraviolet shielding rate while ensuring good near-infrared shielding rate.
[0058] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
[0059] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A method for preparing a near-infrared shielding coating with high visible light transmittance, characterized in that: It includes the following steps: The concentration of 1-10% H x The WO3·2H2O blue powder solution and the polyvinyl butyral ester powder are fully mixed in a mass ratio of 1:5-10 to obtain a slurry, and then the slurry is applied on the surface of the glass sample by spin coating, and finally dried to obtain a glass coating, wherein 0≤x≤1; The H x The preparation method of WO3·2H2O blue powder solution is as follows: (1) Pretreatment: LaO3H3 powder and benzyl alcohol are mixed in a mass ratio of 1:500-1000, and stirred until the LaO3H3 powder is completely dissolved to obtain a LaO3H3 solution; (2) Preparing a precursor solution: mixing the LaO3H3 solution in step (1) with the WCl6 raw material in a mass ratio of 20-40:1, and mixing by magnetic stirring to obtain a precursor solution; (3) High temperature reaction: placing the precursor solution in step (2) in a reaction kettle, and then placing the reaction kettle in a microwave synthesizer, reacting under the combined action of hydrothermal and microwave, the reaction temperature is 50-200°C, the reaction time is 5-240min, and then naturally cooling to room temperature to obtain a reaction solution; (4) Separation and washing: The reaction solution in step (3) is centrifuged, and the separated solid is then washed with deionized water, anhydrous ethanol, dilute sulfuric acid, ionized water and anhydrous ethanol in sequence to obtain the H x WO3·2H2O blue powder solution; the H x The particle size of WO3·2H2O blue powder is 5-100nm.
2. The method for preparing a near-infrared shielding coating with high visible light transmittance according to claim 1, characterized in that: The stirring conditions in step (1) are as follows: the stirring speed is 100-800 r / min.
3. The method for preparing a near-infrared shielding coating with high visible light transmittance according to claim 1, characterized in that: The stirring conditions in step (2) are as follows: the stirring speed is 100-800 r / min, and the stirring time is 10-60 min.
4. The method for preparing a near-infrared shielding coating with high visible light transmittance according to claim 1, characterized in that: The centrifugal separation conditions in step (4) are: rotation speed of 3000-5000 r / min, time of 2-10 min.
5. The method for preparing a near-infrared shielding coating with high visible light transmittance according to claim 1, characterized in that: The method of washing with ionized water in step (4) is as follows: the separated solids are washed with deionized water in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
6. The method for preparing a near-infrared shielding coating with high visible light transmittance according to claim 1, characterized in that: The method of washing with anhydrous ethanol in step (4) is as follows: the separated solid and anhydrous ethanol are washed in an ultrasonic cleaner for 5-30 minutes, and then placed in a centrifuge at a speed of 3000-5000 r / min for centrifugation for 2-10 minutes.
7. The method for preparing a near-infrared shielding coating with high visible light transmittance according to claim 1, characterized in that: The method of washing with dilute sulfuric acid in step (4) is as follows: the separated solid is washed with dilute sulfuric acid having a concentration of 20-30% in an ultrasonic cleaner for 5-30 minutes, and then centrifuged in a centrifuge at a speed of 3000-5000 r / min for 2-10 minutes.
Citation Information
Patent Citations
Method for preparing cesium-tungsten bronze material at normal pressure
CN112299484A
Preparation method of superfine cesium tungsten bronze powder
CN117566797A
Near-infrared-shielding ultrafine particle dispersion body, near-infrared-shielding intermediate film, near-infrared-shielding laminated structure, and production method for near-infrared-shielding ultrafine particle dispersion body
CN110662817A